Radiography students' perceptions of Peer assisted learning. Issue 2 (May 2020) - Elshami, W.; Abuzaid, M.; Abdalla, M.E.
Abstract: Introduction: Peer Assisted Learning (PAL) is collaborative learning in which students from the same or different academic levels learn from each other. It is meant to support the regular teaching and learning process. Learning in PAL can be explained by constructive social learning theories and has many advantages such as, students' perception of it and the ease of discussion between peers. This study aims to measure students' perception of PAL in the context of radiography education. Methods: A PAL programme was implemented in one module taught to second year radiography students. A questionnaire was then distributed to the participating students (n = 28) to measure their perception of PAL; the questionnaire consisted of 13 questions with a Likert scale of 5 (1 = strongly disagree to 5 = strongly agree). The results were analysed using SPSS to calculate the percentages, means, standard deviations, and factorial analysis. Results: Twenty-six students responded to the questionnaire (92.8%). The range of agreement in all questionnaire items ranged from 79.9% to 92.3%. The factor analysis revealed two main factors affecting students' acceptability. PAL enriched students' learning experience and helped them in preparation for exams. Conclusion: The use of PAL is highly acceptable by students in context of radiography education. Implications for practice: More studies are necessary to confirm the best methods of using PAL. These may involve both students and educators, and pre- and post-methods.